Relationship Between Left Ventricular Myocardial Longitudinal Mechanics and In-hospital Heart Failure in Patients With Acute Myocardial Infarction: a Two-dimensional Speckle-tracking Study - Khuyag, Batmyagmar; Chimed, Surenjav; Baldandorj, Amarjargal; Zundui, Lkhagvasuren; Davaakhuu, Narantuya (Central Asian Journal of Medical Sciences, 2016)
Objectives: In-hospital heart failure (HF) during acute myocardial infarction (AMI) is associated with adverse outcome. However, data about the relationship between left ventricular (LV) longitudinal myocardial mechanics and in-hospital HF in patients with AMI is limited. Thus, we aimed to determine the association between speckle-tracking derived global longitudinal strain (GLS) and in-hospital HF. Methods: We selected patients with AMI treated by primary percutaneous coronary intervention (PCI). In-hospital HF was defined by Killip class. Multiple logistic regression analysis was used to reveal the relationship between LV GLS and in-hospital HF. Results: A total of 414 patients (mean age 60 ±13 years, 84% male) were included and in-hospital HF presented in 93 patients (22.5%). LV GLS was significantly impaired in patients with in-hospital HF compared to patients without (-16.1 ±3.7% vs. -11.6 ±3.1%, p<0.001). After adjustment of possible predictors, GLS was independently associated with in-hospital HF (odds ratio 1.32, 95% CI: 1.16-1.50, p<0.001). In-hospital HF presented in 21 patients with preserved left ventricular ejection fraction (LVEF) and GLS was also significantly impaired (-17.7 ±3.2% vs. -12.7 ±2.2%, p<0.001). Separate multiple logistic regression models showed that GLS was still independently associated with in-hospital HF in this group. Conclusion: LV GLS is independently associated with in-hospital HF during AMI. This relationship is still evident for patients with preserved LVEF.